Protocolo para screening de habilidades musicais - Koga, Fabiana Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The perceptual-sensory musical abilities are at the basis of music talent. Knowing them will allow access to part of this complex phenomenon composed of different nuances in order to contribute to the initial recognition of talented children and young people in music. Unfortunately, there is no music education in all Brazilian schools, even with a federal decree that establishes this, it is low the rate of procedures that are dedicated to the identification, evaluation and enrichment of people with music talent. Based on this context, if the school cooperated with the screening of music talent and direct the identified students to multimodal evaluations or projects and out-ofschool institutions (music schools) or allow the development of music activities inside school (curricular adaptions and groupings) and if music wasn’t understood only as entertainment, many talented students in music would not be at music education’s margin and music professionalization. So a screening for musical abilities built for Brazilian reality, for elementary school, primary education, according to psychophysical method of peer comparison would be able to initially map, revealing music talent cases? Based on these questions, this thesis aimed to build and instrument to screening (mapping) music abilities according to psychophysical method of peer comparison able to map initially music talents. For this purpose, there was initially in Study1 a systematic review around the construct, in Study 2, other to list the properties and component attributes of the construct, then, in Study 3 the construction of the Protocol for Screening Music Abilities. The instrument counts on 127 items distributed in eight dimensions (timbre, height, melody, intensity, harmony, agogic, length and rhythmic pattern). The instrument was submitted to judges specialized in music, applied in pilot project, received amendments and it was finally applied in eight schools from the countryside of São Paulo. 411 students from public schools and 242 students from private schools participated of the empiric application of the instrument. All of them aged from six to 11 years old, enrolled in 1st and 5th grades. The data analysis followed the criteria: converting the answers to scores, analysis of the validity of the instrument through W Kendell, item analysis using chi-square test, binominal test and the students with better and fewer results were identified. The Kruskall-Wallis statistics tests were used to compare the groups and the Wilcoxon test for intergroup analysis. In conclusion, Protocol for Screening Music Abilities was able to screen music talent initially, however, future refining procedures will be necessary to adjust those items that presented problems and even readjust the levels of application, considering the performance of the participants by performance range.

As habilidades musicais percepto-sensoriais estão na base do talento musical. Conhecê-las possibilita acessar parte desse fenômeno complexo e composto por diferentes nuances, com a finalidade de contribuir para a identificação inicial de crianças e jovens talentosos em música. No Brasil, no momento desta tese, não havia Educação Musical em todas as escolas, apesar de haver decreto federal que institui tal ensino, e é baixo o índice de procedimentos que se dedicam à identificação, à avaliação e ao enriquecimento de sujeitos com talento musical, os quais são público da Educação Especial. Com base nesse contexto, se a escola colaborasse com o rastreamento do talento musical e encaminhasse os estudantes identificados para avaliações multimodais ou projetos e instituições extraescola (escolas especializadas em música) ou permitisse o desenvolvimento de atividades musicais intraescola (adaptações curriculares e agrupamentos) e se a música não fosse compreendida como entretenimento apenas, muitos estudantes talentosos em música não estariam à margem da educação musical e da profissionalização musical. Então, um screening de habilidades musicais construído para a realidade brasileira, para o ensino fundamental, anos iniciais, de acordo com o método psicofísico de comparação por pares, daria conta de realizar um mapeamento, revelando, de modo inicial, casos de talento musical? Com base nessas questões, o objetivo da presente tese foi construir um instrumento para screening (mapeamento) de habilidades musicais, de acordo com o método psicofísico de comparação por pares, capaz de rastrear, de modo inicial, o talento musical. Para esse fim, houve, inicialmente, no Estudo 1 uma revisão sistemática em torno do construto; no Estudo 2, outra, para elencar as propriedades e atributos componentes do construto; e, depois, no Estudo 3, a construção do Protocolo para Screening de Habilidades Musicais. O instrumento conta com 127 itens distribuídos em oito dimensões (timbre, altura, melodia, intensidade, harmonia, agógica, duração e padrão rítmico). O instrumento foi submetido ao julgamento de juízes especializados em música, aplicado em projeto piloto, recebeu emendas e finalmente aplicado em oito escolas do interior de São Paulo. Participaram da aplicação empírica do instrumento 411 estudantes da rede pública de ensino e 242 da rede particular. Todos tinham idades entre 6 e 11 anos e estavam matriculados no 1º ao 5º ano do ensino fundamental, anos iniciais. A análise de dados seguiu os seguintes critérios: conversão das respostas em escore, análise da validade do instrumento mediante W de Kendell, análise de item utilizando o teste estatístico qui-quadrado, teste binomial e identificaram-se os participantes com melhor e menor rendimento. Foram utilizados os testes estatísticos Kruskall-Wallis, para comparar os grupos e Wilcoxon, para análise intergrupo. Em conclusão, o Protocolo para Screening de Habilidades Musicais conseguiu rastrear o talento musical inicialmente, porém serão necessários procedimentos futuros de refinamento para adequar os itens que apresentaram problemas e, inclusive, readequar os níveis de aplicação, considerando o desempenho dos participantes por faixa de desempenho.
Protocol for screening music abilities
Keywords: Education; Special education; Music education; Talent; Music abilities; Educação; Educação especial; Educação musical; Talento; Habilidades musicais